ANALISIS PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 16 SURABAYA - BELLA YOLANDA CANTA PUTRI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
The study aims to determine the evaluation tools used and the reasons teachers use evaluation tools in class XI IPS SMA Negeri 16 Surabaya. The second study objective was to determine the feasibility of the evaluation tool. This research is quantitative descriptive research approach. Results of the study is an evaluation tool that is used in the form of type written test multiple choice or description. The rationale is to measure the level of understanding of students and adjust the type of material that has been presented both theory and analysis. As for the results of the feasibility study is based on an expert evaluation tool that the evaluation tool used in SMA Negeri 16 Surabaya overall decent. Keywords: Using, Tool, Evaluation, Accounting, SMA